Local approach and FEM in brittle fracture prediction - Kozák, Vladislav; Dlouhý, Ivo (Computer Assisted Methods in Engineering and Science, 2023)
Local approach in fracture mechanics is based on the application of appropriate failure micromechanistic models to make predictions of fracture behaviour. The FEA of crack-tip and an associated post-processing routine is usually applied. Here should be noted the distinction between the cells of material, having characteristic microstructural dimensions, which constitute the cleavage process zone, and the corresponding finite elements used to represent their behaviour. Predictions of brittle fracture are based on the Beremin local approach model, where the Weibulliocation parameter Qu and shape parameter m have been calculated using FEM for Charpy type specimen. These parameters are considered to be transferable material properties, independent of temperature, specimen geometry or loading mode and can be used for prediction of the stress intensity factor K.